Legal protection of street children as a result of economic exploitation based on the child rights convention 1989 - Vallencia Paramitha; Sukardi Sukardi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Child protection is all activities to guarantee and protect children and their rights so that they can live, grow and develop, and participate optimally, in accordance with human dignity and protection from violence and discrimination. The purpose of this paper is to find out the synchronization between Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and the 1989 Convention on the Rights of the Child . The result of this writing is Presidential Decree No. 36/1990 on Ratification of the Convention on the Rights of the Child, not in accordance with Law No. 24/2000 on International Covenants. In this case, the 1989 Convention on the Rights of the Child concerning the Rights of the Child, where the object of the Convention is a "child" which should be an important part of state affairs and ratified in the form of a law.